1996
DOI: 10.1159/000169049
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dosage Ibopamine Treatment in Progressive Renal Failure: A Long-Term Multicentre Trial

Abstract: A multicentre trial (11 nephrology centres) was carried out to test the effects of ibopamine, an orally active dopamine-like drug, on the progression of chronic renal failure. For a 2-year period 189 chronic renal failure patients (serum creatinine level 1.5-4.0 mg/dl) were observed. They were homogeneous for basic nephropathy, degree of residual renal function, blood pressure, and proteinuria. the patients were randomly divided into two groups: 96 took ibopamine at a dosage of 100 mg/day (group A) and 93 serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Data transfer required even more intense follow-up with time from agreement to data transfer ranged from 9 to 108 weeks, and number of contacts ranged from 3 to 31, with a mean of 11. Of the 70 studies contacted, we did not receive a reply from seven authors [28,[30][31][32][33][34][35], 13 studies were disqualified after initial discussion with the authors [25,[36][37][38][39][40][41][42][43][44][45][46][47], the data was never received for 7 studies despite initial agreement [27,29,42,[48][49][50][51] and 9 studies were disqualified after data were received for insufficient data [14,[52][53][54][55][56][57][58][59], leaving 34 studies included in the dataset (Table 2, second, third and fourth columns) [15,17,19,22,26,42,43,. Overall, more than 3 years have passed since the first author contact to the transfer of the last dataset.…”
Section: Creation Of a Patient-level Pooled Databasementioning
confidence: 99%
“…Data transfer required even more intense follow-up with time from agreement to data transfer ranged from 9 to 108 weeks, and number of contacts ranged from 3 to 31, with a mean of 11. Of the 70 studies contacted, we did not receive a reply from seven authors [28,[30][31][32][33][34][35], 13 studies were disqualified after initial discussion with the authors [25,[36][37][38][39][40][41][42][43][44][45][46][47], the data was never received for 7 studies despite initial agreement [27,29,42,[48][49][50][51] and 9 studies were disqualified after data were received for insufficient data [14,[52][53][54][55][56][57][58][59], leaving 34 studies included in the dataset (Table 2, second, third and fourth columns) [15,17,19,22,26,42,43,. Overall, more than 3 years have passed since the first author contact to the transfer of the last dataset.…”
Section: Creation Of a Patient-level Pooled Databasementioning
confidence: 99%
“…The median follow up time in these trials was 3 years with a range of 1.3 to 4.6 years. About 83% trials were in the setting of diabetes mellitus and 6 trials (33%) included patients with CKD (stage III or more and/or macroalbuminuria) [18], [22], [23], [25], [30], [31], [35], [39], [41], [43], [46], [53], [55], [60], [66], [67], [70]. The overall quality of studies included was good.…”
Section: Resultsmentioning
confidence: 99%
“…Stefoni et al 2 conducted a prospective, randomised, open‐label, multicentre trial of ibopamine in patients with mild‐to‐moderate chronic kidney disease CKD (plasma creatinine 1.5–4.0 mg/dL). A total of 189 patients from 11 nephrology centres were randomly allocated to receive ibopamine 100 mg omni die (n = 96) or no treatment (n = 93).…”
Section: What Is the Evidence?mentioning
confidence: 99%
“…There have been one randomised controlled trial (RCT) 2 and three prospective, non‐controlled trials 3–5 (all but 1 trial was reported by the same group).…”
Section: What Is the Evidence?mentioning
confidence: 99%